Retrospectroscope Horatio B. Williams and the first electrocardiographs made in the United States. - Geddes, L.A.
Horatio Burt Williams was likely the first American clinical electrophysiologist. He published the first paper on ECG in the western hemisphere, constructed the first string galvanometer in America, plotted the first vectorcardiogram, discovered the ventricular vulnerable period, and first quantitated the amount of 60-Hz current required to produce ventricular fibrillation with body-surface electrodes; he also showed that ventricular defibrillation could be achieved with body-surface electrodes using high-intensity 60-Hz current. Williams died at the age of 78 on November 1, 1955, at the Presbyterian Hospital in New York. He was born on September 17, 1877, in Utica, New York
Keywords: 60 Hz; 78 y; America; ECG; Horatio B. Williams; United States; Body-surface electrodes; First electrocardiographs; High-intensity 60-Hz current; Medical equipment history; String galvanometer; Ventricular fibrillation; Ventricular vulnerable period; Western hemisphere